Experimental study of the influences of different factors on the acid-rock reaction rate of carbonate rocks. (July 2023) - Fan, Yu; Peng, Huan; Chen, Gang; Peng, Junliang; Han, Huifen; Qin, Yi; Wang, Liang; Liu, Dan
Abstract: The Sichuan Basin's carbonate gas reservoirs require stimulation. Non-uniform etched fractures are created as a result of the violent interaction between reservoir cores and an acidic fluid, and these fractures provide pathways for the flow of oil and gas. Focusing on the long distance and high conductivity of acid fracturing, in this study, based on the geological characteristics of the carbonate rocks in the Sichuan Basin and engineering requirements, a rotary disc instrument was used to conduct an experimental study of the acid-rock reaction rate under different temperature (40 °C, 65 °C, 90 °C, 115 °C, 150 °C), acid concentrations (12 %, 16 %, 20 %, 24 %), rotation speeds (125 rpm, 208 rpm, 291 rpm, 375 rpm), common ion effect values, and types of acid (conventional acid, gelled acid, diverted acid, cross-linked acid), focusing on the changes in the acid-rock reaction rate with the various parameters. The research shows that conventional acid had the fastest acid-rock reaction rate, which was 1.85 times that of the gelled acid, 1.94 times that of the diverted acid, and 3.03 times that of the cross-linked acid. To obtain a correct understanding of the acid-rock reaction kinetics, experimental investigation of the effects of the various parameters on the reaction rate is essential. Highlights: To analyze the geological characteristics of Longwangmiao carbonate reservoir in Anyue, Sichuan Basin Uses the rotating disk apparatus to study acid-rock reaction rate of carbonate rocks. Research the effects of temperature, acid concentration, rotation speed, the common ion effect, and acid type on the acid-rock reaction rate. To clarify the effect of different on the reaction rate of acid rock